The stem cells of small intestinal crypts: where are they? - Potten, C. S. (Cell Prolif, 2009)
Recently, there has been resurgence of interest in the question of small intestinal stem cells, their precise location and numbers in the crypts. In this article, we attempt to re‐assess the data, including historical information often omitted in recent studies on the subject. The conclusion we draw is that the evidence supports the concept that active murine small intestinal stem cells in steady state are few in number and are proliferative. There are two evolving, but divergent views on their location (which may be more related to scope of capability and reversibility than to location) several lineage labelling and stem cell self‐renewing studies (based on Lgr5 expression) suggest a location intercalated between the Paneth cells (crypt base columnar cells (CBCCs)), or classical cell kinetic, label‐retention and radiobiological evidence plus other recent studies, pointing to a location four cell positions luminally from the base of the crypt The latter is supported by recent lineage labelling of Bmi‐1‐expressing cells and by studies on expression of Wip‐1 phosphatase. The situation in the human small intestine remains unclear, but recent mtDNA mutation studies suggest that the stem cells in humans are also located above the Paneth cell zone. There could be a distinct and as yet undiscovered relationship between these observed traits, with stem cell properties both in cells of the crypt base and those at cell position 4.